(untitled) (Research, Society and Development, 2022)
Tilapia production is among the fastest-growing fish farming activities worldwide. Feeding is among the main factors that impact the cost of production, representing about 70 to 80% in intensive rearing systems, with protein being the most expensive nutrient in the diet. Thus, the application of alternative sources that reduce feed production costs becomes relevant for the fish production chain. Dried Distillers Grains With Solubles (DDGS) are by-products obtained by the fermentation process of ethanol and can be used in animal diets. Its use in tilapia feeding began to be explored as an alternative source to replace soybean meal or fish meal in the ration, based on that, the objective of this literature review was to approach the use of DDGS in tilapia diets under the point of view of productive performance, immune responses and intestinal morphology.